The development of speed-power qualities of schoolchildren with different typologies applying coordination training - G.G. Polevoy (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Purpose : to determine the influence of coordination abilities on the development of speed-power qualities in 7-8 years old schoolchildren with a different type of nervous system. Material : the pedagogical experiment was conducted in a regular school and lasted 7 months. The study involved children 7-8 years old (n = 60). All schoolchildren were differentiated into 3 groups (in each group - n = 20). Coordination abilities were determined by the test "3x10 shuttle run". Speed- power qualities were determined by the test "Standing Long Jump". The strength of the nervous system was diagnosed according to the "Tapping test" method. Results : it was determined that it is necessary to develop the coordination abilities of 7-8 years old schoolchildren. It was determined the interrelation of coordination abilities and speed-power qualities. It was confirmed the effectiveness of a differentiated approach based on the typology of children. The results were realized at physical education lessons at school. Conclusion : it is recommended to develop coordination abilities during 12-15 minutes in physical education classes for schoolchildren. Such training will be more effective if consider the typology of the nervous system of schoolchildren.